Joint multicast routing and channel assignment for multi-radio multi-channel wireless mesh networks with hybrid traffic. (15th February 2017) - Wang, Jihong; Shi, Wenxiao
Abstract: In this paper, joint multicast routing and channel assignment problem in wireless mesh networks (WMNs) with hybrid traffic is investigated. Previous works design routing and channel assignment schemes for WMNs with single multicast session, however, resource usage is optimized for only one multicast session in this case and overall network load balance is left out of consideration. This may result in high congestion in some links, while others are underutilized. In this paper, multicast routing and channel assignment problem is solved from traffic management perspective by introducing load balance. Programming formulation is formulated to obtain the optimal results which can be used as benchmark to evaluate other schemes. Multicast weighted conflict graph is designed to model partially overlapped channels (POCs) interference in hybrid traffic scene. It regards links originating from the same node as one transmission to fully exploit wireless broadcast advantage; it uses link weight to measure interference degree and gives full consideration to interference characteristics of POCs. A heuristic multicast routing and channel assignment scheme based on multicast weighted conflict graph is designed to solve the joint problem, and simulation results show that the heuristic scheme can reduce network interference and improve WMNs service capability while dramatically reducing computational complexity.